2004
DOI: 10.1136/ip.2003.003889
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hip fracture in protected and unprotected falls in nursing homes in Norway

Abstract: Objectives: To compare the probability of hip fracture in protected and unprotected falls in a real world setting in nursing homes. Design: Observational study. Setting: Seventeen nursing homes (965 beds) in Norway. Subjects: All residents in the nursing homes with at least one fall during the intervention period. Intervention: Hip protectors were introduced as a regular part of the health care service for all the residents for an intervention period of 18 months. Residents who were considered high risk were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…While there is controversy about the efficacy of hip protectors from clinical studies (Koike et al, 2009;Kiel et al, 2007;Parker et al, 2006;Forsen et al, 2004;Birks et al, 2004;O'Halloran et al, 2004;van Schoor et al, 2003;Meyer et al, 2003;Harada et al, 2001;Kannus et al, 2000;Chan et al, 2000;Lauritzen et al,1993), this is thought to be due largely to poor adherence in wearing the device, and there is general agreement that they reduce fracture risk if worn at the time of a fall (Cameron et al, 2001(Cameron et al, , 2010(Cameron et al, , 2003Robinovitch et al, 2009;Ekman et al, 1997). However, additional evidence is required to understand the factors that influence both adherence and biomechanical performance.…”
Section: Introductionmentioning
confidence: 93%
“…While there is controversy about the efficacy of hip protectors from clinical studies (Koike et al, 2009;Kiel et al, 2007;Parker et al, 2006;Forsen et al, 2004;Birks et al, 2004;O'Halloran et al, 2004;van Schoor et al, 2003;Meyer et al, 2003;Harada et al, 2001;Kannus et al, 2000;Chan et al, 2000;Lauritzen et al,1993), this is thought to be due largely to poor adherence in wearing the device, and there is general agreement that they reduce fracture risk if worn at the time of a fall (Cameron et al, 2001(Cameron et al, , 2010(Cameron et al, , 2003Robinovitch et al, 2009;Ekman et al, 1997). However, additional evidence is required to understand the factors that influence both adherence and biomechanical performance.…”
Section: Introductionmentioning
confidence: 93%
“…12 The second paper concluded that persons at high risk of hip fracture in nursing homes may decrease the risk to one third by wearing a hip protector in a fall. 13 Many studies have shown that the percentages of acceptance and daily use of hip protectors are often low because many elderly people find the protector uncomfortable when resting and cumbersome when dressing and undressing. 11 14 15 These studies were randomised controlled trials that investigated the effect of hip protectors to prevent hip fractures in nursing homes.…”
mentioning
confidence: 99%
“…Data from studies powered to evaluate hip protectors is consistent: hip protectors reduce hip fracture incidence by more than a half (best results were reported in Norwegian nursing homes, 69%) [55]. They have no influence on other fractures.…”
Section: Common Risk Factors For Fallsmentioning
confidence: 61%
“…[29]. The incidence of falls and hip fractures in residential elderly patients can be reduced with a multifactorial interdisciplinary prevention program (MIPP) [30][31][32][33][34][35][36][37][38][39][40]:…”
Section: Common Risk Factors For Fallsmentioning
confidence: 99%